WLE/ICRAF co-led report with recommendations on soil carbon management and monitoring accepted by the UNCCD Conference of the Parties - CGIAR Research Program on Water, Land and Ecosystems (2019)
The recommendations of a technical report produced by a team co-led by WLE/ICRAF on soil carbon management and monitoring was adopted by the 197 country parties at the UNCCD COP14.